Soil fusaria from oil palm habitats in Malaysia - Ho, Yin Wan; Varghese, George (Universiti Pertanian Malaysia, 1985)
Fusarium species were isolated from 22 sampling sites in 4 oil palm plantations located in different regions of Peninsular Malaysia using Peptone-PCNB medium. Eight species and two varieties of Fusarium viz., F. solani, F. oxysporum, F. oxysporum var. redolens, F. semitectum, F. moniliforme, F. moniliforme var. subglutinans, F. equiseti, F. longipes, F. lateritium and F. heterosporum were isolated. Among these, F. solani and F. oxysporum were the most prevalent species followed by F. semitectum and F. moniliforme. The other 5 species and 2 varieties of Fusarium were of sporadic occurrence. Generally, soils from areas with young palms had larger number and greater variety of Fusarium species when compared to soils from mature and old palm areas. The rhizosp here soil contained a greater variety of Fusarium species than soils in the avenue of palms (non-rhizosphre soil).